MPC-20 CLINICAL AND MOLECULAR FEATURES OF GLIOBLASTOMAS ARISING IN THE SETTING OF LI FRAUMENI SYNDROME. (3rd December 2022) - Kibe, Yuji; Ohka, Fumiharu; Aoki, Kosuke; Motomura, Kazuya; Yamaguchi, Junya; Maeda, Sachi; Nishikawa, Tomohide; Shimizu, Hiroki; Saito, Ryuta
Abstract: Introduction: Li Fraumeni Syndrome (LFS) is a rare autosomal dominant tumor predisposition syndrome caused by germline alterations of the TP53 . Brain tumors are included in LFS core cancers. Choroid plexus carcinomas and medulloblastomas tend to present in pediatric LFS patients, while gliomas tend to present in adult LFS patients. There are few previous reports about gliomas arising in the setting of LFS. Here, we report clinical and molecular features of three cases of glioblastoma arising in the setting of LFS. Results: Mean age at diagnosis was 40 years (range: 32-45). Two patients were male. Two patients had medical history of multiple tumors and family history of brain tumors. Magnetic resonance imaging of each patients revealed a left cerebellar peduncle lesion, a right parietal lobe lesion and two lesions in the pons and right parietal lobe, respectively. Pathological diagnoses of all cases were glioblastomas, IDH-wildtype. All patients underwent chemoradiotherapy after surgery. Mean progression free survival was 10.4 months (range: 5.1-17.0). All patients were admitted to palliative care mean 17.3 months (range: 14.4-21.4) after diagnosis. All patients had heterozygous germline mutations of TP53 . Genetic analysis of tumor tissues revealed TP53 mutation and PDGFRA amplification in all patients. In all cases, mutation spots of TP53 in tumor-derived DNA were consistent with those of germ line mutations. In all cases, copy number alteration of TP53 gene in tumor-derived DNA were not detected. EGFR amplification, the combination of gain of chromosome 7 and loss of chromosome 10 (7+/10-) and mutations of IDH, H3F3A, BRAF genes and TERT gene promoter were not detected in all tumor-derived DNA. Conclusion: We experienced three cases of glioblastoma, IDH-wildtype arising in the setting of LFS. Clinical courses of all cases were poor. Notably, all tumor tissues harbored TP53 mutation and PDGFRA amplification, while no tumor tissues harbored TERTp mutation, EGFR amplification and 7+/10-.